2023
DOI: 10.1186/s12936-023-04504-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individual, household and environmental risk factors for malaria infection on Bioko Island to inform interventions

Abstract: Background Since 2004, malaria transmission on Bioko Island has declined significantly as a result of the scaling-up of control interventions. The aim of eliminating malaria from the Island remains elusive, however, underscoring the need to adapt control to the local context. Understanding the factors driving the risk of malaria infection is critical to inform optimal suits of interventions in this adaptive approach. Methods This study used individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Indoor residual spraying takes place in houses across Bioko Island, the largest island of Equatorial Guinea with an area of about 2000 km 2 . The population is urban, with 85% of the island’s 270,000 inhabitants living in the capital of Malabo [ 16 ]. Malaria is endemic with perennial transmission on Bioko; before project implementation the Plasmodium falciparum parasite rate was 45% in 2–14 year-old children and has since declined by about 75% [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indoor residual spraying takes place in houses across Bioko Island, the largest island of Equatorial Guinea with an area of about 2000 km 2 . The population is urban, with 85% of the island’s 270,000 inhabitants living in the capital of Malabo [ 16 ]. Malaria is endemic with perennial transmission on Bioko; before project implementation the Plasmodium falciparum parasite rate was 45% in 2–14 year-old children and has since declined by about 75% [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Malaria prevalence in Nigeria differs across geopolitical regions because of the varying environmental and seasonal settings that affect the reproductive patterns of mosquito vectors. The prevalence of malaria is primarily a function of its underlying transmission intensity (Alegana et al 2013 ), which in turn is propelled by indicators such as interventions (García et al 2023 ), environmental and climatic factors (Ekpa et al 2023 ; Rivera and Gutiérrez 2023 ), and socio-economic and demographic characteristics (Ogunsakin and Chen 2020 ; Pourtois et al 2023 ; Rivera and Gutiérrez 2023 ). In malaria prevalence research, authors have linked malaria rates to environmental and socio-economic factors like population density and potential evapotranspiration (PET) (Yang et al 2012 , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Travellers are common sources of imported malaria. For instance, a prevalence survey in the low-burden island of Bioko, Equatorial Guinea, showed that malaria infection was highly related with having a history of travel to mainland Equatorial Guinea [ 11 ]. In PNG, the haplotypes of P. vivax isolates from different regions revealed patterns of transmission following major human migration routes, especially within the ‘Islands region’ of PNG [ 12 ].…”
Section: Introductionmentioning
confidence: 99%